2015
DOI: 10.1590/1809-4392201403663
|View full text |Cite
|
Sign up to set email alerts
|

Espectro polínico da própolis de Scaptotrigona aff. postica (Hymenoptera, Apidae, Meliponini) em Barra do Corda, MA, Brasil

Abstract: A própolis é uma substância resinosa coletada por abelhas de diferentes partes de uma planta, portanto, sua qualidade é relacionada à sua origem botânica. O objetivo deste trabalho foi verificar se os tipos polínicos encontrados indicam a origem botânica de suas resinas e contribuir com o conhecimento da relação destas abelhas com a vegetação do entorno do meliponário. Foram realizadas 31 coletas ao longo de 12 meses, com intervalo de sete dias entre elas. Os grãos de pólen foram extraídos da própolis e utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
(14 reference statements)
0
6
0
5
Order By: Relevance
“…The most frequent pollen types found were Borreria verticillata, Anadenanthera sp. and Mimosa caesalpiniifolia (Souza et al, 2015). Amongst the pollen types, 34 unique pollen types occurred in a given month of the year, which were characterized as seasonal indicators of flowering species, influenced by seasonal and interannual variations in climate (Souza et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent pollen types found were Borreria verticillata, Anadenanthera sp. and Mimosa caesalpiniifolia (Souza et al, 2015). Amongst the pollen types, 34 unique pollen types occurred in a given month of the year, which were characterized as seasonal indicators of flowering species, influenced by seasonal and interannual variations in climate (Souza et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…and Mimosa caesalpiniifolia (Souza et al, 2015). Amongst the pollen types, 34 unique pollen types occurred in a given month of the year, which were characterized as seasonal indicators of flowering species, influenced by seasonal and interannual variations in climate (Souza et al, 2015). Much research has been carried out using cardanol, suggesting different types of applications for this compound and its derivatives (Barbosa et al, 2019;Mubofu & Mgaya, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the growth habit of melliferous plants and the climate influences the flowering season and causes herbs and lianas to flower mainly in summer and autumn (January to June) and trees and shrubs in the spring (late September to December). There is availability of nectar and pollen throughout the year, with supply decreasing in the winter months (July to September) 07 Souza et al [17] Both the quantitative and qualitative analyses of the pollen types found in the propolis of Scaptotrigona aff. were valuable for their characterization.…”
Section: N°bibliographic Referencementioning
confidence: 99%
“…Segundo Souza et al (2015), S. aff. postica possui a preferência pelo forrageamento da espécie arbórea Borreria verticillata da família Rubiaceae.…”
Section: Introductionunclassified